The morphological characterization of the of dry and germinated Morinda citrifolia L. (Rubiaceae – Rubioideae) seed - Paula, Stelamaris; Sousa, João; Brito, Edy; Gallão, Maria (Revista Ciência Agronômica, 2016)
Information about the morphology, chemical composition and reserve mobilization is important in understanding the establishment of native and exotic species. The purpose of this study was to describe the morphology, chemical composition, and mobilization of reserves during germination of noni (Morinda citrifolia L.). Biometric and morphological analyzes were performed with 100 randomly selected dried seeds. Other seeds were treated with sulfuric acid PA and soaked in Petri dishes. Collected seeds of five different times of germination were used for cytochemical and chemical analysis. For cytochemical analysis, the cuts of 5μm were submitted to dyes TB at pH 4.0; XP at pH 2.5, reaction of PAS and Sudan IV. The seeds were crushed for chemical analysis with lipids, proteins and soluble sugars extraction that were determined gravimetrically, by the Bradford method and the Antrona method, respectively. The fatty acid composition of the dry seed was determined by gas chromatography. Noni seeds are albuminous and have a thick seed coat, rich in lignin. Lipid and protein bodies were observed inside the endosperm cells, representing 43.50% and 9.15% respectively, while the reservoir of soluble sugars was less than 5%. Linoleic acid was the most prevalent with 68.1%. The lipids were mobilized during germination, suffering a reduction of up to 38% of its total. Proteins, as well as lipids decreased by 25.78% during the germination period observed. The main reserves of noni seeds are lipids and proteins that are mobilized during germination to provide energy and matter to the developing embryo and synthesis of more complex compounds.